Combined method for simultaneous morphology, immunophenotype and karyotype (MAC) in leukemias - Chauffaille, Maria de Lourdes Lopes Ferrari; Coutinho, Vicente; Yamamoto, Mihoko; Kerbauy, José (São Paulo Medical Journal, 1997)
In the present study, a combined method (CM) for attaining simultaneous identification of leukemic cell morphology, karyotype and immunophenotype has been evaluated in 21 patients with acute leukemia and 1 with CML in blast crisis were studied for morphology, citochemistry, immunophenotype and karyotype. Karyotype was performed in a bone marrow sample by using conventional techniques. In each case, direct method (DM) and/or three cultures were tried. The CM consisted in separating a small part of the material resulting from any of the cultures or DM, preparing slides through cytospin and immunophenotyping through APAAP method using the same monoclonal antibodies (MoAb) as for diagnosis. In 14 cases, the metaphases proved positive to the MoAb: in 4, the cells with abnormality had their origin defined; in other 4 the karyotype was normal preventing any identification; 6 cases had minimal abnormalities not visible through CM; and in two cases abnormal karyotypes were detected only in the cultures with GM-CSF. This study showed that CM is feasible in cases where evident numerical or structural chromosomal abnormalties are present.